Explaining MPs' perceptions of voters' positions in a party-mediated representation system: evidence from the portuguese case - Belchior, Ana Maria (2013)
The article addresses the crucial but still relatively understudied issue of political perceptions, specifically the perceptions of members of parliament (MPs) regarding the positioning of voters on the left–right spectrum, and the accuracy thereof. It focuses on the Portuguese case, which differs from others studied to date in terms of the links between MPs and voters (in contrast to prior research, Portuguese voters do not vote for an MP candidate but for a party list; the representation process is mediated by political parties). The article begins by characterizing Portuguese MP perceptions of voters’ left–right positions, and then explores the reasons for MPs’ perceptual accuracy. The findings show that MP perceptions are shaped by wishful thinking, reiterating previous research, and that party integration is an important new factor explaining perceptual accuracy.